MUTASI TITIK F1534C GEN VOLTAGE GATED SODIUM CHANNEL (VGSC) PADA Aedes aegypti DI KELURAHAN PANCUR PUNGAH (JAMBI MEDICAL JOURNAL "Jurnal Kedokteran dan Kesehatan", 2020)
The incidence of dengue hemorrhagic fever (DHF) has increased significantly throughout the world in the last decade. One of the challenges in eradicating DHF is the occurrence of vector resistance to insecticides. This study aimed to looked at the mutation site of the VGSC codon F1534C Aedes aegypti on RT 5 & 6 Pancur Pungah Village, Muara Dua District, Ogan Komering Ulu Selatan Regency as a marker of resistance. The samples in this studied were larvae and pupae of Aedes aegypti. Larvae and pupae were bred into F1 generation and then tested for susceptibility and followed by polymerase chain reaction (PCR). The results of the suscepbillity test carried out obtained mosquito mortality of 10.5% so it was categorized resistant based on WHO criteria. Continued PCR test found no mutation point occurred in the VGSC gene mutation point F1534C in Aedes aegypti. Therefore, the possibility of mutations in the VGSC gene is at another mutation point.